TINJAUAN LITERATUR: AKTIVITAS FARMAKOLOGI DAN KANDUNGAN SENYAWA DARI KACANG KEDELAI (Glycine max L.) - Sadino, Asman; Apriani, Riza; Solihah, Puspa Sari Dewi; Rachmawati, Siti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Soybean (Glycine max L.) is a functional food from the legume group that is rich in bioactive compounds and has the potential to prevent degenerative diseases. This review aims to assess the content of the main active compounds and pharmacological activities of soybeans based on current scientific evidence. The method used is narrative review through literature searches on Google Scholar and PubMed databases of full-text articles published in the period 2010-2025. Articles included were in vitro and in vivo experimental studies that addressed the compound content and pharmacological activity of soybeans, while review articles, proceedings, and irrelevant publications were excluded. From the selection process, 12 articles were obtained that met the criteria for analysis. The results showed that isoflavones are the dominant compounds in soybeans that play a role in various pharmacological activities that can be grouped into several main categories, namely antioxidant and anti-inflammatory activities, metabolic activities (antidiabetes, antiobesity, and antihyperuricemia), and cardiovascular activities (antihypertension and anticholesterol). In addition, soy also shows potential as a supportive agent in the prevention of cancer and osteoporosis. Based on these findings, soy has great potential to be developed as a functional food and therapeutic support material in the prevention of degenerative diseases.